Synthesis, Characterization, Electrochemistry and Biological Activities of Ni(II) and Cu(II) Complexes of Schiff Bases¶ - GURUBASAVARAJ, P.M.; VEERESHA SHARMA, P.M. (Asian Journal of Chemistry, 2010)
Some metal complexes of nickel(II) and copper(II) with Schiff bases have been prepared in an ethanolic medium and characterized by elemental analysis and molecular weight determination. The IR observations suggest that the ligands have coordinated through azomethine nitrogen atoms and reacted through hydroxy group. The magnetic susceptibility data along with electronic and ESR spectra indicates a distorted octahedral structure for the Cu(II) and Ni(II) complexes. Biological activity studies have also been presented.